High sensitivity thermometry using Yb3+/Er3+ co-doped LuNbO4 nanoparticles over a wide temperature range. (June 2022) - Wang, Zhen; Liu, Ronghui; Yin, Yanzhen; Dou, Chao; Hu, Chen; Wang, Yanshuang; Teng, Wenying; Niu, Qiuyan; Zhu, Jiaxiu; Zheng, Fei; Che, Yang; Li, Jianhong; et al.
Abstract: Improving the sensitivity of thermometry systems is an important objective. In this study, the modified molten salt method was used to prepare Yb 3+ /Er 3+ co-doped LuNbO4 nanoparticles with uniform size and morphology. By considering the 2 H11/2 and 4 S3/2 levels of Er 3+ ions as the thermal coupling energy levels, an up-conversion thermometer based on LuNbO4 :5 mol% Yb 3+ and 1 mol% Er 3+ nano-phosphor was implemented with the fluorescence intensity ratio read-out method. The experimental results indicated that the LuNbO4 :5 mol% Yb 3+, 1 mol% Er 3+ nanoparticles exhibited excellent optical thermometric sensitivity. The maximum absolute sensitivity and relative sensitivity were 0.0084 K –1 (at 673 K) and 11.34 %K −1 (at 93 K), respectively. The high absolute sensitivity may be attributed to the relatively high phonon energy of LuNbO4 (−807 cm −1 ), and the relative sensitivity increased with the difference in the energy level between thermally coupled levels. The temperature measurements obtained using LuNbO4 :5 mol% Yb 3+, 1 mol% Er 3+ nanoparticles exhibited excellent repeatability, and luminescence thermometry could be implemented over a wide temperature range of 93–673 K. Our experimental results indicate that LuNbO4 :5 mol% Yb 3+, 1 mol% Er 3+ nanoparticles have potential applications in high-sensitivity optical thermometry over a wide temperature range, and they are also ideal candidates for use in thermometers. Highlights: Yb 3+ /Er 3+ :LuNbO4 nanophosphors with uniform size and morphology prepared. High optical thermometric relative sensitivity (11.34 %K −1 ) and absolute sensitivity (0.0084 K –1 ) achieved. Excellent repeatability and wide temperature measurement range of 93–673 K.